Dynamism, Capital Structure, and Performance in a Sub-Saharan Economy: Extending the Institutional Difference Hypothesis - Ofori-Dankwa, Joseph; Julian, Scott D. (Organization Science, 2013)
Extant research examining the capital structure–performance relationship has been undertaken primarily in developed economies. These studies integrate agency theory considerations with the contingency perspective and suggest a positive interaction between sector dynamism, equity, and performance. Our study extends this research stream by examining the capital structure–performance link in a sub-Saharan economy, an underresearched but economically emerging region. Using logic undergirding a substantial stream of institutional theory-based studies that we term the institutional difference hypothesis, we argue that the implications of the capital structure–performance relationship are contingent on the extent of national-level institutional underdevelopment. Taking into account institutional differences between developed economies and those in the sub-Saharan region, we hypothesize a negative interaction between sector dynamism, equity, and firm performance in sub-Sahara. Using longitudinal data from Ghanaian corporations for 1996–1999, we find substantial support for our hypothesis. Contrary to findings from developed economies, sector dynamism negatively moderates the firm equity–performance relationship: a strongly positive effect of equity on performance in stable sectors becomes slightly negative in highly dynamic ones. We unpack the implications of these results for theory and research.